Uranium spatio-temporal variability in groundwater: an environmental risk assessment case study - Albuquerque, M. T. D. (2015)
Uranium in the environment results from natural geochemical processes and human activities. The discharges of uranium and associated radionuclides as well as metals and metalloids from waste and tailing dumps in uranium mining areas and processing sites pose contamination risks to surface and groundwater. Uranium is one of the most widespread contaminant in groundwater from mining areas. Uranium and associated trace elements spatial distribution patterns in groundwater, within the transboundary watershed of the Águeda River (Portugal-Spain) is the main purpose of the herein work. Uranium minerals and associated sulphides occur distributed in the Águeda river watershed, with a potential source of contamination. These mineral resources were exploited in the past and were abandoned without any recovered processes. Seventy-five groundwater samples were selected, georeferenced and collected in the Águeda watershed in June 2012. For each water point were analyzed “in situ” parameters (temperature, pH, electrical conductivity, Eh, dissolved oxygen) and trace element contents, such is uranium, were determined by inductively coupled plasma coupled mass (ICP-MS). Groundwater’s uranium spatial distribution were obtained using geochemical and geostatistical approaches, such are geostatistical modeling and associated simulations with spatial uncertainty evaluation. The spatial map shows that higher uranium content clusters (U hot spots) are concentrated in the central area of the Águeda watershed, associated with the proximity of the mineralizations and overlapping the old mine activities sites. In the northern and southern parts of the Águeda watershed, could be identified clusters of moderate to high U contents, with simulated uranium hot spots showing high variability. These highly uranium content clusters and uncertain hot spots should be carefully monitored in future work. The obtained results indicate that the old U-mining activities as a serious environmental risk factor in the Agueda´s watershed. These results were crossed with the vulnerability assessment DRASTIC index of the studied watershed, overlapping with moderate to high vulnerability areas. These overlapping of U contents distribution and vulnerability maps allow the identification of areas with an increased risk of contamination. The spatial U distribution maps showed to be suited for assessing the environmental impact associated with old mine activities and facilitate the improvement of local groundwater systems’ management, with adequate monitoring activities, and remediation possibilities.